MANAJEMEN PROGRAM PELATIHAN DAN PENGEMBANGAN BAHASA ARAB - Umar Manshur (Nurul Jadid University, 2015)
The success of an educational institution can not be separated from the role of a teacher as a resource that should be developed and enhanced professionalism. Therefore, the role of an institution is very important in improving the pedagogical ability of educators, because a good education institution is an institution that is able to grow and develop in accordance with the demands of the times, and to face the times must be supported by the quality of professional teachers. Increased professionalism of teachers with the training and development should also be managed properly in order to function well against the individual, organization, or society.